A memória dos militantes gráficos do Rio de Janeiro sobre o golpe civil-militar de 1964 - Cristiane Muniz Thiago (Ciências Sociais Unisinos)
This paper discusses the struggle over the memory of one of the most remarkable episodes of the Brazilian recent history, the 1964 civil-military coup. Our investigation focuses on the militants of the Union of Printer Workers of Rio de Janeiro and their memories about the events that culminated in the 1964 coup. The construction and reconstruction of the memory of that period and its linkage with the printers' political issues will be discussed in the text. Our analysis takes into account interviews with old militants and Journals of the category. We conclude that in the face of an impending political-institutional crisis, especially after the 1964 coup, the elements that sustain the printers' identity construction are driven and negotiated. This memory, which is part of a historical experience of the group, is also reconstructed in the present to legitimize or contradict the role of social actors who still occupy prominent positions in the Union organization.